Case report: The CT features of pediatric retroperitoneal extrarenal Wilms tumor: a report of two cases and literature review - Li, Ting; Wang, Haoru; Chen, Xin; He, Ling (Frontiers in Pediatrics, 2023)
Retroperitoneal extrarenal Wilms tumor is a rare condition in children, which can be easily misdiagnosed as other retroperitoneal malignancies unrelated to renal origin. Computerized tomography scan plays a crucial role in diagnosing and distinguishing retroperitoneal malignancies. In this report, we present two cases of retroperitoneal extrarenal Wilms tumor in children who were admitted due to abdominal mass. Laboratory examination did not reveal any significant abnormality. However, computerized tomography scan revealed a solid or cystic-solid mass in the retroperitoneum, accompanied by a bone spur extending from the anterior edge of the vertebral body to the back of the mass, while the origin of the tumor remained unclear. By analyzing these two cases and reviewing previous studies on retroperitoneal extrarenal Wilms tumor in children, we summarized the clinical and imaging characteristics of this rare condition. We also found that the presence of a spinal deformity adjacent to the mass might indicate the possibility of retroperitoneal extrarenal Wilms tumor.